DOP74 Initial Clearance of infliximab is a predictor for the time of formation of anti-drug antibodies. (27th May 2021) - Kutschera, M; Primas, C; Reinisch, S; Novacek, G; Kim, S H; Lee, S H; Lee, J H; Reinisch, W; Mould, D R
Abstract: Background: Treating patients with biologics like infliximab (IFX), may cause the formation of antidrug antibodies (ADA). ADA are associated with faster drug clearance, reduced treatment efficacy and increased risk of infusion-related side effects. The aim of this study is to identify possible predictors for ADA-formation. Methods: A time to first detection of ADA model was developed by using data from a Phase 3 clinical trial of biosimilar CT-P13 and originator infliximab comparing efficacy and safety in moderately to severely active Crohn's disease (CD). We analyzed data from 220 patients initiating IFX. Seven subjects with ADA present at baseline were discarded. The following baseline covariates were evaluated in this analysis: age, weight, first estimated drug clearance, disease duration, dose, sex and concomitant immune-modulators. Continuous covariates were divided into lower quartile, inter-quartile range, and upper quartile bins. Kaplan-Meier survivor estimates were plotted by bin. The data was then modeled parametrically with NONMEM by constructing a full model which was further refined using the Wald's Approximation Method algorithm. Hazard ratios and probability of ADA at time points of interest were calculated for significant covariates. Results: Initial IFX clearance, concomitant immunomodulators and IFX dose were identified as being statistically significant predictors of the time to first ADA. The model suggested that the hazard of ADA increases by 61% for every increase on 0.1 L/day in clearance, it decreases by 41% with concomitant administration of immunomodulators and decreases by 29% for every increase in dose of 100 mg. Thus, for a patient with initial IFX clearance of 0.2 L/day, no immunomodulators and a dose of 328 mg, the average time to first ADA is 374 days (range 221–451). If clearance is 0.4 L/day under the same conditions, then ADA onset is 144.5 days (range 90–216). Increasing the starting dose to 428 mg would improve the time to onset to 203 days (range 110–337). Again, under the same conditions, adding immunomodulator would increase the time to onset to 354 days (range 214–451). Conclusion: We have identified initial infliximab clearance as an independent predictor for onset of ADA in CD patients. Our results suggest that early assessment of clearance should guide treatment optimization with IFX in patients with CD, including the addition of concomitant immunosuppressants or increasing the dose during induction.